Identity markers: Interpreting sod-house occupation in Sandwich Bay, Labrador - Rankin, Lisa (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2015)
Documentary evidence suggests that Inuit were present in the Strait of Belle Isle by the late 16th century, yet the archaeological evidence for Inuit settlement in southern Labrador is sparse. Inuit sites are difficult to recognize south of Nunatsiavut, where 19th-century Inuit-Métis families and seasonal Newfoundland fishers occupied settlements that leave similar archaeological surface-traces. In 2009 a SSHRC-funded Community-University Research Alliance was initiated to examine Inuit history in southern Labrador. One of the primary goals of the research was to develop archaeological criteria to distinguish between these ethnically distinct settlements. This paper presents the results from several seasons of research in Sandwich Bay, Labrador. It uses data from community interviews, archaeological surveys, and excavations at four Inuit settlements, one Inuit-Métis house, and one Newfoundland fishery camp to help resolve the issue of site ethnicity for the area immediately south of Hamilton Inlet. Site location and house and site features are used to increase confidence in Inuit site classification and to provide strategies for targeted test-excavations elsewhere in southern Labrador and on the Quebec North Shore. The results of the research also allow for a better understanding of the nature and extent of Inuit occupation in Sandwich Bay.